Surgical complexity score as a predictor of surgical site infection in dentoalveolar surgeries (Research, Society and Development, 2023)
Introduction: Postoperative surgical site infections represent one of the most frequent complications related to health care and can increase morbidity and mortality, in addition to increasing treatment costs. Objectives: This study evaluated surgical site infections incidence after dentoalveolar surgeries of retained third molars. The article presents the development of a surgical complexity score that can be used as a predictive method for surgical site infections risk in dentoalveolar surgeries. Methodology: In this cross-sectional observational study, the sample was obtained for convenience, from medical records of patients diagnosed with tooth retention and who underwent dentoalveolar surgery of third molars, from 2015 to 2020. Demographic variables of patients, characteristics of the surgery and information regarding the diagnosis of surgical site infections in the postoperative period were collected. Results: A total of 360 medical records were analyzed, with 59 surgical site infection cases diagnosed (16.4%).  There was a statistical difference (p